BERAGAMA BAHAGIA UNTUK BINA DAMAI: KAJIAN ATAS TEORI KEMATANGAN BERAGAMA WILLIAM JAMES - Ismail, Roni (UIN Sunan Kalijaga Yogyakarta, 2024)
In the ideal or normative terms, all religions teach the tenet of peace, so that they express a